Endometrial immune assessment in patients with a history of previous euploid blastocyst failure - Garratt, Jemma; Mohammadi, Baharak; Al-Hashimi, Balsam; Linara-Demakakou, Elena; Bhattacharya, Rukma; Ahuja, Kamal K.; Macklon, Nick; Rahmati, Mona (Frontiers in Immunology, 2025)
BackgroundInflux and establishment of key endometrial immune factors in the mid-luteal phase of the menstrual cycle is paramount for successful embryo implantation. Endometrial immune dysregulation is associated with repeated embryo implantation failure and miscarriage. In in vitro fertilisation cycles, approximately 30% of embryos diagnosed as chromosomally normal will still fail to produce a viable live birth, yet factors such as the endometrium are rarely clinically explored.MethodsIn this retrospective analysis, clinical outcomes were compared between patients undergoing their first euploid transfer in a conventional substituted cycle (n=612), patients undergoing a euploid transfer in a similar cycle after previous euploid failure (n=149) and the study group of patients with previous euploid transfer failure who received a modified endometrial preparatory regimen following endometrial immune profiling targeting uterine natural killer cell recruitment, maturity and activity as well as their key regulatory counterparts (n=37).ResultsSignificant differences were found between first euploid attempt outcomes and patients with previous failures who didn’t use endometrial testing (implantation rate 63% vs 51, P=0.02; clinical pregnancy rates 55% vs 40%, P=0.002; live birth rates 50% vs 38%, P=0.02). Patients with previous failures who underwent endometrial immune profiling and a subsequent personalised plan exhibited a trend towards improved clinical outcomes than those with previous failures and no testing (implantation rate 65% vs 51%; clinical pregnancy rate 57% vs 40%; live birth rate 54% vs 38%, respectively) although statistical significance was not demonstrated. Clinical outcomes were comparable between the endometrial immune profiling group and those undergoing a first euploid attempt (implantation rate 65% vs 63%; clinical pregnancy rate 57% vs 55%; live birth rate 54% vs 50%, respectively).ConclusionsPatients who had a failed attempt when using a euploid embryo had lower chances of pregnancy when repeating their treatment, unless they received a personalised endometrial preparation regimen derived from the results of endometrial immune profiling. These preliminary findings indicate the potential value of guiding management based on immune endometrial testing.